(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
The problem of word semantics occupies a significant place at the center of linguistic research. At the same time, the development of socio-economic relations, the improvement of the material environment, and the advancement of scientific knowledge impose fundamentally new practical and theoretical tasks on linguists in the processing and systematization of linguistic material. Against the background of such challenges, linguists are required to pay particular attention to terminological studies, especially to the identification of the constituent elements of terminological systems, namely terms as words with specialized meanings. These needs are associated not only with the trends in the development of scientific knowledge but also with the growing demand for high-quality translation and adequate intercultural communication.